Bibliometric analysis of bone metastases from lung cancer research from 2004 to 2023 - Tang, Jing; Gu, Zhangui; Yang, Zongqiang; Ma, Long; Liu, Qiang; Shi, Jiandang; Niu, Ningkui; Wang, Yanyang (Frontiers in Oncology, 2024)
Background Bone metastases of lung cancer (BMLC) severely diminish patients’ quality of life due to bone-related events, and the lack of clear guidelines globally regarding medical and surgical treatment significantly reduces patient survival. While knowledge about BMLC has grown exponentially over the past two decades, a comprehensive and objective bibliometric analysis remains absent. Methods A comprehensive bibliometric analysis was conducted on relevant literature on BMLC extracted from the Web of Science database from 2004 to 2023 by Biblioshiny, VOSviewer, Scimago Graphica, CiteSpace, and Microsoft Office Excel Professional Plus 2016 software. 936 papers related to BMLC were extracted from the Web of Science Core Collection (WoSCC). The number of publications, countries, institutions, global collaborations, authors, journals, keywords, thematic trends, and cited references were then visualized. Finally, the research status and development direction in the last 20 years were analyzed. Results This study included a total of 936 papers on BMLC from 2004 to 2023. There has been a steady increase in global publications each year, peaking in 2021. China had the highest number of publications, followed by Japan and the United States. Additionally, China had the most citations with an H-index of 35, while the US followed with an H-index of 34, highlighting their significant contributions to the field. “Frontiers in Oncology” had the highest number of publications. CiteSpace analysis identified “lung cancer,” “bone metastasis,” and “survival” as the top high-frequency keywords, encapsulating the core research focus. Keyword clustering analysis revealed six main clusters representing the primary research directions. Burst analysis of keywords showed that “skeletal complications” had the highest burst intensity from 2005 to 2013, while recent research trends include “immunotherapy” and “denosumab,” with bursts from 2021 to 2023. Trend topic analysis indicated that “non-small cell lung cancer,” “immunotherapy,” and “immune checkpoint inhibitors” represent the cutting-edge research directions in this field. Conclusion This article reveals the current status and trend of research on BMLC, which is increasing worldwide. China and the United States have contributed the most, but international cooperative research on BMLC should be strengthened. The pathogenesis, early prevention, and individualized treatment of BMLC need to be strengthened for further study, and immunotherapy is the next hotspot of lung cancer bone metastasis research.